EFEKTIVITAS MEDIASI DALAM MENYELESAIKAN SENGEKTA PADA MASYARAKAT DI KELURAHAN MALEBER DAN KECAMATAN ANDIR, BANDUNG - Gunardi Lie; Moody R. Syailendra; Mia Hadiati; Indah Siti Aprilia (PROSIDING SERINA, 2021)
In terms of disputes resolution, there are various alternative forms of dispute resolution outside the court. One form of dispute resolution that is often used is Mediation. Mediation is the embodiment of deliberation for consensus in dispute resolution. In the mediation process, dispute resolution begins with the good faith of both parties in resolving the dispute amicably. This can be realized because mediation prioritizes the approval of both parties without any coercion from the mediator. The Supreme Court has issued Regulation of the Supreme Court of the Republic of Indonesia Number 1 of 2016 concerning Mediation Procedures in Courts as legal basis on conducting mediation in Courts. However, mediation not only can be carried by the Court, but mediation can also be carried out by the community outside the Court on various disputes faced by the community. Village officials, RT/RW, Lurah, and other respected person in the community can act as mediators in resolving disputes in the community. The research method used in this research is Empirical. The study was conducted to see the efectivity of mediation in resolving community disputes, especially in the Maleber and Andir sub-districts. The results of the study show that consensus deliberation mediation can resolve problems/disputes faced by the community without having to go through the litigation process. Local government officials such as Lurah, Camat, and local officials have played a major role in resolving disputes in the community.